Transmission of Küme Mogen in the Indigenous Chihuimpilli Community, Freire Municipality, Araucanía Region, as a Contribution to Intercultural Education (Revista INTEREDU11, 2024)
The native peoples or indigenous peoples offer us from their cultural values, some perspective to live well, harmonies and balance in different aspects of life. One of the knowledge areas of the Mapuche cosmovision (worldview) that interests us and we want to explore is the Küme Mogen. The Küme Mogen has provided us with a great contribution to intercultural education. The values ​​of Küme Mogen or good living that encompass four dimensions individual, social, ecosystem, and spiritual. The four dimensions above have a great contribution to today's heterogeneous society, to live in harmony, mutual respect, and healthy coexistence (healthy good relationship). And this must be experienced from now on in the educational community as a privileged place for the training of the future generation. Thus, we set ourselves three objectives: Describe the principles, roles, and practices of the Küme Mogen, of the Mapuche families and authorities in the Chihuimpilli indigenous community. Identify the level of knowledge of the teachers' management team and the indigenous community about the Küme Mogen to be incorporated as an essential element of the Institutional Educational Project (IEP). Finally, is to propose to the Chihuimpilli Community School, to incorporate the principles of Küme Mogen in the IEP, to strengthen intercultural education. The qualitative research used some methods: semi-structured interviews, and Focus Groups. The non-probabilistic sample was made up of 15 people, six teachers and nine elderly people from the community. The outcomes of the research indicate that the values are so important, but in reality, the community concern is that the important values are less practice in the life of the new generation on one hand. On the other hand, the education community has put these values into practice in very informal ways, but the educational community has not included yet them in the Institutional Educational Project.
Keywords: Good living; Mapuche Indigenous community; Worldview; Institutional educational project; Intercultural education; cultural value